Unjuk Kerja Sistem Pendingin Adsorpsi Dengan Pasangan Karbon Aktif-Metanol Sebagai Adsorben-Adsorbat - Ivand Hintingo; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The air conditioning system that we used now may contribute to the effects of global warming and high energy consumption. One solution is to use the adsorption cooling system. Adsorption refrigeration system using activated carbon as adsorbent and methanol as adsorbate aims to replace the existing cooling system today. Targets to be achieved in this research is to analyze the adsorption cooling system that can replace vapor compression system that uses a refrigerant that can damage the ozone layer, with vartiation of desorption time and the mass flow rate of water in the evaporator to see its effect on the value of the COP on the system. Adsorbate or refrigerant used in the cooling system is methanol and adsorbent used in adsorption cooling system is activated carbon. The method used in this study is experiment. Experiment method conducted to determine the effect of desorption time variations and variations in the mass flow rate of water in the evaporator to the value of the COP. The highest COP is the variation of water mass flow rate 0,016 kg / s that is 0,099.Key Word : Adsorption, COP, Activated Carbon, Methanol, Desorption Time